AYURVEDIC MANAGEMENT OF VICHRCHIKA W. S. R TO ECZEMA - D. Khot, Jitendra; K. Jadhav, Dnyaneshwar. (International Journal of Ayurveda and Pharma Research, 2015)
Today modern medical science have lots of facilities & technologies for treatment of patient even though many diseases may still in progressive phase in the society. Vicharchika is one of such kind of disorders. In Ayurveda context, eleven types Kshudra kushtha are described and Vicharchika is one of them. In ancient text, there described many lines of treatments of Vicharchika like leech application, local application and many oral medicines. Eczema is a skin disease, which is observed as exfoliation of the skin, mostly accompanied by severe itching. In the chronic stages, there may be oozing of pus and bleeding from the affected regions. This case is a example of Vicharchika like skin disease can be managed with Ayurvedic therapy. The combination of certain Ayurvedic drug such as Manjista, Daruharidra, Khadir, Arogyavardhini, etc is effective for the management of Vicharchika (Eczema).